ABS environmentally friendly laser engraving material for electronic keyboard and preparation method thereof
By adding components such as PC and radium engraving powder to ABS environmentally friendly radium engraving materials to form composite materials, the problem of unstable performance when recycling ABS is solved, and the mechanical performance and service life of electronic keyboards are improved.
Patent Information
- Application Number
- CN202410654736.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-05-24
AI Technical Summary
Recycling ABS When producing ABS radium sculptures for use in electronic keyboards, the impurities are high and the performance is unstable, which leads to problems such as damage and cracking of the electronic keyboard, reducing the service life.
By adding PC, lactic powder, lubricant, anti-aging agent and compatibility to ABS environmentally friendly radial engraving materials, the composite material is formed to improve its mechanical properties and compatibility.
It improves the mechanical properties and aging resistance of ABS environmentally friendly radium engraving materials, so that the electronic keyboard used for production has better mechanical properties, reduces the possibility of damage and cracking, and extends the service life.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present application relates to the field of ABS laser engraving materials, and more specifically, to an ABS environmentally friendly laser engraving material for electronic keyboards and a preparation method thereof. Background Art
[0002] ABS plastic is a ternary copolymer of acrylonitrile (A), butadiene (B), and styrene (S). The relative content of the three monomers can be changed arbitrarily to make various resins. ABS plastic has the common properties of the three components. A makes it resistant to chemical corrosion and heat, but its surface hardness is lower than that of PC. B makes it highly elastic and tough. S makes it have the processing and molding characteristics of thermoplastics and improves electrical properties. At the same time, ABS also has better processing fluidity. Therefore, ABS plastic has been widely used in manufacturing industries such as machinery, electronic products, textiles, automobiles, aircraft, ships, and chemical industries.
[0003] Usually, laser carving powder is added to ABS to produce ABS laser carving materials. ABS laser carving materials can be used in the production of electronic keyboards. Laser carving, also known as laser engraving, is a process of surface treatment based on optical principles. Electronic keyboards use ABS laser carving materials. After laser carving, the surface carving is clear. The product has good gloss, the whiteness of the engraved fonts is good, and it will never fall off.
[0004] With the progress of science and technology, people's environmental awareness is getting higher and higher. Therefore, it is imperative to promote green environmental protection. Therefore, recycled ABS is used instead of synthetic ABS to reduce carbon emissions and make it green and environmentally friendly. However, the recycled ABS has a lot of impurities, unstable performance, and low mechanical properties, especially toughness. Therefore, after the ABS laser engraving material produced by the recycled ABS is used for the production of electronic keyboards, the electronic keyboards are prone to damage, cracking, etc. during use, which reduces the service life of the electronic keyboards. Therefore, it is necessary to further study the ABS environmentally friendly laser engraving material. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides an ABS environmentally friendly laser engraving material for electronic keyboards and a preparation method thereof.
[0006] In a first aspect, the present application provides an ABS environmentally friendly laser engraving material for an electronic keyboard, comprising the following raw material components in parts by weight:
[0007] Recycled ABS: 50-80 pieces
[0008] PC: 5-10 copies
[0009] 2-5 portions of laser engraving powder
[0010] 1-3 parts lubricant
[0011] Anti-aging agent 0.1-0.3 parts
[0012] 2-5 parts of compatibilizer;
[0013] The laser carving powder is composed of rare metal oxides, silicates and glass fibers.
[0014] The composition and usage ratio of the above raw materials are the best choices for this application. Among them, recycled ABS has the advantages of ABS characteristics and green environmental protection. PC is polycarbonate, also known as PC plastic; it has the advantages of colorless transparency, heat resistance, impact resistance, flame retardant BI level, better wear resistance than ABS, good mechanical properties, etc. Therefore, by compounding PC and recycled ABS and combining their properties, ABS environmentally friendly laser engraving materials have both good mechanical properties and the advantages of green environmental protection, while lubricants can further improve the processing performance of ABS environmentally friendly laser engraving materials, and anti-aging agents improve the aging resistance of ABS environmentally friendly laser engraving materials.
[0015] The compatibilizer can reduce the resistance of the contact interface between PC and recycled ABS, reduce the particle size of the dispersed phase, increase the surface area of the dispersed phase, improve the combined force between the dispersed phase and the continuous phase, stabilize the dispersed phase, and thus form a stable alloy between PC and recycled ABS. At the same time, the compatibilizer can also improve the compatibility of laser engraving powder and ABS environmentally friendly laser engraving material raw material system.
[0016] The laser engraving powder composed of rare metal oxides, silicates and glass fibers not only has a fluorescent effect, but also can further improve the mechanical properties of ABS environmentally friendly laser engraving materials.
[0017] In summary, this application compounds PC with recycled ABS and, under the action of a compatibilizer, improves the mechanical strength of the alloy. The laser engraving powder composed of rare metal oxides, silicates, and glass fibers not only has a fluorescent effect, but also can further improve the mechanical properties of the ABS environmentally friendly laser engraving material. With the assistance of lubricants and anti-aging agents, the ABS environmentally friendly laser engraving material has the advantages of good mechanical properties and green environmental protection. Therefore, the electronic keyboard used for production has better mechanical properties, reduces the possibility of damage and cracking during use, and increases the service life of the electronic keyboard.
[0018] Preferably, the weight ratio of the rare metal oxide, silicate and glass fiber is 1:(1-3):(2-6).
[0019] When the weight ratio of rare metal oxides, silicates and glass fibers is 1:(1-3):(2-6) for compounding, the obtained laser engraving powder has a better filling and reinforcing effect, and the obtained ABS environmentally friendly laser engraving material has a better fluorescent effect and mechanical properties. Therefore, the electronic keyboard produced by the ABS material can reduce the occurrence of damage and cracking of the electronic keyboard and improve the durability of the electronic keyboard.
[0020] Preferably, the rare metal oxide is yttrium oxide and / or zirconium oxide; the silicate is one or more of white carbon black, hollow glass microspheres, and potassium aluminum silicate.
[0021] The above-mentioned yttrium oxide and zirconium oxide have better fluorescence effect, and can also play the role of filling and toughening; while white carbon black, hollow glass microspheres, and potassium aluminum silicate can play a reinforcing and toughening role. Therefore, compounding through rare metal oxides, silicates, and glass fibers can also play better filling, reinforcing, fluorescence and other effects. Therefore, the obtained ABS environmentally friendly laser engraving material has better mechanical properties, further reducing the possibility of damage, cracking, etc. in electronic keyboards produced by ABS environmentally friendly laser engraving materials.
[0022] Preferably, the compatibilizer is a maleic anhydride compatibilizer.
[0023] Preferably, the compatibilizer is composed of maleic anhydride graft and macromolecular coupling agent in a weight ratio of (1-4):1.
[0024] The use of maleic anhydride compatibilizers can further improve the compatibility of PC and recycled ABS, while the macromolecular coupling agent can improve the compatibility of laser powder, PC and recycled ABS, and also promote the compatibility of PC and recycled ABS, thereby making the obtained ABS environmentally friendly laser engraving material have better mechanical properties.
[0025] Preferably, the maleic anhydride grafted material is one or more of POE-g-MAH, maleic anhydride grafted EVA, maleic acid rosin resin, and polyvinylidene fluoride grafted maleic anhydride.
[0026] Maleic acid rosin resin is an ultra-light-colored, stable maleic acid modified rosin resin developed by addition reaction of rosin and maleic anhydride and esterification with pentaerythritol / glycerol, through refining, decolorization, modification and other processes. Maleic acid rosin resin has the advantages of anti-aging and good compatibility with polymers.
[0027] POE-g-MAH is a POE molecule with a strongly polar side group (maleic anhydride) introduced into the main chain. Therefore, maleic anhydride grafted POE can become a bridge to enhance the adhesion and compatibility between polar and non-polar materials. Therefore, it can improve the compatibility of PC and ABS.
[0028] Polyvinylidene fluoride grafted with maleic anhydride has the advantages of toughening, weathering resistance, UV resistance, flame retardancy, toughening, insulation, etc. At the same time, the maleic anhydride it contains can further increase the capacity and promote the compatibility of PC and recycled ABS.
[0029] Maleic anhydride grafted EVA has the function of promoting polymer compatibility and at the same time has better bonding strength, making the structure of the alloy material stable.
[0030] Therefore, using maleic anhydride grafted materials as one or more of POE-g-MAH, maleic anhydride grafted EVA, maleic acid rosin resin, and polyvinylidene fluoride grafted maleic anhydride as compatibilizers can have a capacity-increasing effect and promote the compatibility of PC and ABS, thereby improving the mechanical properties of the ABS environmentally friendly laser engraving material obtained after the alloy, and when it is used to produce electronic keyboards, the possibility of breakage during use is reduced.
[0031] Preferably, the maleic anhydride grafted material is composed of the following raw materials in parts by weight:
[0032] Maleic anhydride grafted POE-g-MAH: 0.5-2 parts
[0033] Maleic anhydride grafted EVA: 0.5-1.5 parts
[0034] Maleic acid rosin resin: 0.1-0.5 parts
[0035] Polyvinylidene fluoride grafted maleic anhydride: 0.4-1 part.
[0036] When POE-g-MAH, maleic anhydride grafted EVA, maleic acid rosin resin, and polyvinylidene fluoride grafted maleic anhydride are compounded, a synergistic effect is achieved, thereby making the compatibility of the compatibilizer better. Therefore, the prepared ABS environmentally friendly laser engraving material has better mechanical properties, and the electronic keyboards used in the production are not prone to breakage, cracking, etc.
[0037] Preferably, the macromolecular coupling agent is a copolymer of styrene-butyl acrylate-γ-propyltrimethoxysilane and / or a copolymer of n-butyl acrylate-methyl methacrylate-vinyltriethoxysilane.
[0038] The copolymer of styrene-butyl acrylate-γ-methacrylatepropyltrimethoxysilane and the copolymer of n-butyl acrylate-methyl methacrylate-vinyltriethoxysilane both contain silane and are easily compatible with polymers, thereby improving the compatibility of laser engraving powder with PC and recycled ABS. At the same time, it is easy to be compatible with maleic anhydride grafted products, thereby promoting the compatibility of PC with recycled ABS, and can also improve the bonding strength, making its alloy structure compact, and further improving the mechanical properties of ABS environmentally friendly laser engraving materials.
[0039] Preferably, the anti-aging agent is one or more of UV770, UV-P, antioxidant 1076, and antioxidant 168.
[0040] UV770 and UV-P have anti-ultraviolet aging properties, and antioxidant 1076 and antioxidant 168 have anti-thermal oxidative aging properties. Therefore, using one or more of these compositions can achieve better anti-aging properties.
[0041] Preferably, the lubricant is one or more of pentaerythritol stearate, ethylene distearate, PE wax, and triphenyl phosphate.
[0042] Pentaerythritol stearate, ethylene distearate, PE wax, and triphenyl phosphate all have a lubricating effect, which improves the processing convenience of ABS environmentally friendly laser engraving materials.
[0043] In a second aspect, a method for preparing an environmentally friendly ABS laser engraving material for an electronic keyboard comprises the following steps:
[0044] According to weight parts, the recycled ABS, PC, laser engraving powder, lubricant, anti-aging agent and compatibilizer are weighed and mixed evenly, extruded and granulated to obtain ABS environmentally friendly laser engraving material.
[0045] The above process is simple to operate. By fully mixing the various raw materials, extruding them to make them melt and fully mix them, and granulating them, ABS environmentally friendly laser engraving materials are obtained. When producing electronic keyboards, the ABS environmentally friendly laser engraving materials are further injection molded or molded to form corresponding electronic products.
[0046] In summary, this application has the following beneficial effects:
[0047] 1. This application compounds PC with recycled ABS, and under the action of a compatibilizer, improves the mechanical strength of the alloy. The laser engraving powder composed of rare metal oxides, silicates, and glass fibers not only has a fluorescent effect, but also can further improve the mechanical properties of the ABS environmentally friendly laser engraving material. With the assistance of lubricants and anti-aging agents, the ABS environmentally friendly laser engraving material has the advantages of good mechanical properties and green environmental protection. Therefore, the electronic keyboard used in the production has better mechanical properties, reduces the possibility of damage and cracking during use, and increases the service life of the electronic keyboard.
[0048] 2. Using maleic anhydride grafted POE-g-MAH, maleic anhydride grafted EVA, maleic acid rosin resin, polyvinylidene fluoride grafted maleic anhydride as a compatibilizer can increase the capacity and promote the compatibility of PC and ABS, thereby improving the mechanical properties of the ABS environmentally friendly laser engraving material obtained after alloying. When it is used to produce electronic keyboards, the possibility of breakage during use is reduced.
[0049] 3. When POE-g-MAH, maleic anhydride grafted EVA, maleic acid rosin resin, and polyvinylidene fluoride grafted maleic anhydride are compounded, a synergistic effect is achieved, thereby making the compatibility of the compatibilizer better. Therefore, the obtained ABS environmentally friendly laser engraving material has better mechanical properties, and the electronic keyboards used in the production are not prone to breakage, cracking, etc. DETAILED DESCRIPTION
[0050] The present application is further described in detail below with reference to the embodiments.
[0051] The sources or performance parameters of some raw materials;
[0052] Table 1 Sources or performance parameters of some raw materials
[0053]
[0054]
[0055] The particle size of yttrium oxide, zirconium oxide, white carbon black, hollow glass microspheres, and potassium aluminum silicate in the embodiments of the present application is preferably 500 mesh; the glass fiber has a diameter of 9 μm, an elongation at break of 2.45%, a tensile strength of 1800 MPa, a length of 30 μm, and a specific gravity of 2.6 g / cm 3 .
[0056] Example
[0057] Example 1
[0058] A method for preparing an environmentally friendly ABS laser engraving material for an electronic keyboard comprises the following steps:
[0059] Weigh 50kg of recycled ABS, 5kg of PC, 2kg of laser carving powder (0.5kg of yttrium oxide, 0.5kg of white carbon black, 1kg of glass fiber), 0.5kg of lubricant (pentaerythritol stearate), 0.1kg of anti-aging agent (0.05kg of UV770, 0.05 antioxidant), and 2kg of compatibilizer (POE-g-MAH) and put them into a mixing barrel. Start the agitator to stir the materials in the mixing barrel at a stirring rate of 150r / min and a stirring time of 10min. Then transfer them to a twin-screw extruder for melting and extrusion at a screw speed of 500 rpm. Cool them in a cold water tank, and then enter a 125°C oven for drying for 15s. Then, transfer them to a granulator for granulation to obtain ABS environmentally friendly laser carving materials.
[0060] The temperature settings of the twin-screw extruder are as follows: zone 1 220°C, zone 2 230°C, zone 3 240°C, zone 4 250°C, zone 5 255°C, zone 6 240°C, zone 7 230°C, and die head 235°C.
[0061] Example 2-12
[0062] The difference between Example 2-12 and Example 1 is that the composition and amount of raw materials are different, as shown in Table 2 and Table 3;
[0063] Table 2 Raw material composition and raw material dosage of Examples 1-8 (kg)
[0064]
[0065]
[0066] Table 3 Raw material composition and dosage of Examples 9-12 (kg)
[0067]
[0068]
[0069] Example 13
[0070] The difference between Example 13 and Example 1 is that the compatibilizer is ABS grafted with maleic anhydride.
[0071] Comparative Example
[0072] Comparative Example 1
[0073] The difference between Comparative Example 1 and Example 1 is that the laser carving powder is yttrium oxide.
[0074] Comparative Example 2
[0075] The difference between Comparative Example 2 and Example 1 is that an equal amount of recycled ABS is replaced with ABS (Chi Mei PA-797, Taiwan, China).
[0076] Performance testing
[0077] Test method / test method Tensile strength: refer to ASTM D638, the test condition is 50mm / min, the thickness of the test sample is 2mm.
[0078] Elongation at break: refer to ASTM D638, the test condition is 50mm / min, the thickness of the test sample is 2mm.
[0079] Izod notched impact strength: carried out in accordance with ASTM D256, the test conditions are 2mm V-notch, the temperature is 25°C, and the thickness of the test sample is 3.2mm.
[0080] The above data were tested 3 times and the average value was taken. The specific data are shown in Table 4;
[0081] Table 4 Experimental data of Examples 1-12 and Comparative Examples 1-2
[0082] Test items Tensile strength(Mpa) Elongation at break (%) Impact strength (J / m) Example 1 33.6 23.8 166.3 Example 2 34.7 22.2 168.4 Example 3 35.3 20.1 169.5 Example 4 35.9 24.1 173.2 Example 5 35.5 24.7 174.3 Example 6 37.1 23.1 170.8 Example 7 35.1 23.6 169.7 Example 8 37.8 25.6 174.9 Example 9 38.2 26.8 177.3 Example 10 40.1 26.4 180.2 Embodiment 11 38.9 25.8 179.3 Example 12 41.2 27.6 182.7 Example 13 32.1 21.5 162.8 Comparative Example 1 23.5 18.9 129.6 Comparative Example 2 38.8 25.6 175.9
[0083] Combining Example 1 and Comparative Example 1 and Table 4, it can be seen that the tensile strength, impact strength and elongation at break of Example 1 are all higher than those of Comparative Example 1, indicating that the inorganic filler obtained by compounding rare metal oxides, silicates and glass fibers in the present application, and thus the obtained compatibilizer has better physical properties.
[0084] By comparing Example 1 with Comparative Example 2 and combining with Table 4, it can be seen that the tensile strength, impact strength and elongation at break of Comparative Example 1 are larger than those of Example 1, but the ABS used in Comparative Example 1 is not environmentally friendly.
[0085] By comparing Example 2 with Example 4 and combining with Table 4, it can be seen that the tensile strength, impact strength and elongation at break of Example 4 are all higher than those of Example 1, indicating that the compatibilizer composed of maleic anhydride grafts and macromolecular coupling agents has a better compatibility effect, and the mechanical properties of the obtained ABS environmentally friendly laser engraving material are better, reducing the possibility of damage to the electronic keyboard produced therefrom.
[0086] By comparing Example 5 with Examples 9-11 and combining with Table 4, it can be seen that the tensile strength, impact strength and elongation at break of Examples 9-11 are all higher than those of Example 5, indicating that the compounding of POE-g-MAH, maleic anhydride grafted EVA, maleic acid rosin resin and polyvinylidene fluoride grafted maleic anhydride has a better synergistic effect, thereby making the mechanical properties of ABS environmentally friendly laser engraving materials better.
[0087] By comparing Example 10 and Example 12 and combining with Table 4, it can be seen that the tensile strength, impact strength and elongation at break of Example 12 are all higher than those of Example 10, indicating that when the copolymer of styrene-butyl acrylate-γ-methacrylatepropyltrimethoxysilane and the copolymer of n-butyl acrylate-methyl methacrylate-vinyltriethoxysilane are compounded, a better synergistic effect is achieved, thereby making the compatibility of the ABS environmentally friendly laser engraving material raw material system better, and thus the mechanical properties of the produced electronic keyboard are also better.
[0088] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An ABS environmentally friendly laser engraving material for electronic keyboards, characterized in that: The invention comprises the following raw materials in parts by weight: Recycled ABS: 50-80 pieces PC: 5-10 copies 2-5 portions of laser engraving powder 1-3 parts lubricant Anti-aging agent 0.1-0.3 parts 2-5 parts of compatibilizer; The laser engraving powder is composed of rare metal oxides, silicates, and glass fibers in a weight ratio of 1: (1-3): (2-6); The compatibilizer is composed of a maleic anhydride graft and a macromolecular coupling agent in a weight ratio of (1-3):1; The maleic anhydride grafted material is composed of the following raw materials in parts by weight: POE-g-MAH: 0.5-2 parts Maleic anhydride grafted EVA: 0.5-1.5 parts Maleic acid rosin resin: 0.1-0.5 parts Polyvinylidene fluoride grafted maleic anhydride: 0.4-1 part; The macromolecular coupling agent is a copolymer of styrene-butyl acrylate-γ-methacrylatepropyltrimethoxysilane and / or a copolymer of n-butyl acrylate-methyl methacrylate-vinyltriethoxysilane; The rare metal oxide is yttrium oxide and / or zirconium oxide; the silicate is composed of one or more of white carbon black, hollow glass microspheres, and potassium aluminum silicate.
2. The ABS environmentally friendly laser engraving material for electronic keyboard according to claim 1, characterized in that: The anti-aging agent is one or more of UV770, UV-P, antioxidant 1076, and antioxidant 168.
3. The ABS environmentally friendly laser engraving material for electronic keyboard according to claim 1 is characterized by: The lubricant is one or more of pentaerythritol stearate and PE wax.
4. A method for preparing the environmentally friendly ABS laser engraving material for electronic keyboards as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: According to weight parts, the recycled ABS, PC, laser engraving powder, lubricant, anti-aging agent and compatibilizer are weighed and mixed evenly, extruded and granulated to obtain ABS environmentally friendly laser engraving material.
Citation Information
Patent Citations
PC / ABS alloy heat-conducting insulating nano-composite material and preparation method thereof
CN107501890A
Modified conductive carbon material and preparation method and application thereof
CN116640258A
Macromolecular coupling agent and its preparing process and application
CN1298890A